2009
DOI: 10.1111/j.1755-0998.2008.02168.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐species amplification tests and diversity analysis using 56 PCR markers in Dactylis glomerata and Lolium perenne

Abstract: We report results of cross-species amplification in Dactylis glomerata and Lolium perenne of 12 simple sequence repeats (SSRs) isolated from Lolium multiflorum×Festuca glaucescens, 42 SSRs from Festuca arundinacea and two sequence tagged sites from Oryza sativa. We compared the transferability and diversity between D. glomerata and L. perenne, which are important forage crops. While Nei's gene diversity values were equivalent in both species (from 0.14 to 0.92), the mean number of allele per locus was more imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…When orchardgrass SSR markers were tested for amplification in tall fescue and Lolium species herein, less than 50% had clear and repeatable amplification products. This is consistent with previous efforts to take SSR primers from Festuca and Lolium, and amplify those using orchardgrass DNA (Litrico et al 2009). These differences between Festuca and Lolium and orchardgrass suggest a somewhat unique nature of orchardgrass, and further sequence and marker comparisons among these three genera will likely enlighten the cause for lower relative transferability of markers between Dactylis, Festuca, and Lolium.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When orchardgrass SSR markers were tested for amplification in tall fescue and Lolium species herein, less than 50% had clear and repeatable amplification products. This is consistent with previous efforts to take SSR primers from Festuca and Lolium, and amplify those using orchardgrass DNA (Litrico et al 2009). These differences between Festuca and Lolium and orchardgrass suggest a somewhat unique nature of orchardgrass, and further sequence and marker comparisons among these three genera will likely enlighten the cause for lower relative transferability of markers between Dactylis, Festuca, and Lolium.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have used a variety of tools: chloroplast and ITS sequences have been used to describe phylogenetic relationships (Lumaret et al 1989;Catalan et al 2004;Stewart and Ellison 2010), dominant markers (e.g., RAPD, ISSR, SRAP) used in discreet studies (Koelliker et al 1999;Tuna et al 2004;Peng et al 2008;Zeng et al 2008), and heterologous markers tested from other forage grass species Litrico et al 2009), However, the openplatform dominant markers generally have the inability to add samples to a study without re-analyzing all previous samples due to the large number of bands genotyped per primer. Heterologous marker transferability also decreases as species diverge (Thiel et al 2003;Zhang et al 2005;Litrico et al 2009), and are accompanied by higher likelihood of homoplasy and polymorphism due to mutations that exist among the species (Thiel et al 2003;Saha et al 2004;Zhang et al 2006). Recently, genomic library-derived SSR markers were used to describe relationships among some Asian germplasm (Xie et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…ISSR analysis has been used to assess the genetic diversity of a large number of plant species, including Lolium spp (Dinelli et al, 2004) and Cynodon dactylon (Wang et al, 2013). Both SSRs and ISSRs are powerful and useful tools for genetic studies and have been used in several plant species; however, at present, reports remain P. Madesis et al limited about their use in studies of D. glomerata populations (Litrico et al, 2009;Xie et al, 2010Xie et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The average number of alleles per locus was less than those found for Eugenia dysenterica (10.4) (Zucchi et al, 2002) and Festuca arundinacea (7.8) (Elazreg et al, 2011). The observed number of alleles per locus was closer to the values observed for Hymenaea stigonocarpa (6.43) (Ciampi et al, 2008), Dactylis glomerata (5.45), Lolium perenne (4.50) (Litrico et al, 2009) and Blighia sapida (3.7) (Ekué et al, 2009). Albaladejo et al (2008) suggested that the number of alleles per locus observed for microsatellite loci in Pistacia lentiscus (3-13 alleles) provides highly informative content for the loci in population studies.…”
Section: Characterization Of the Polymorphic Ssr Locimentioning
confidence: 75%
“…Several studies have shown that the homology of DNA sequences in microsatellite flanking-region pairs has allowed SSR markers that have been developed for one species to be transferred to another species of the same genus or even different genera (Zucchi et al, 2002;Ciampi et al, 2008;Ekué et al, 2009;Feres et al, 2009;Litrico et al, 2009;Elazreg et al, Use of SSR markers from A. occidentale to A. humile 2011; Cristofani-Yaly et al, 2011). The success of marker transfer is inversely proportional to the evolutionary distance between the 2 species (Schlotterer et al, 1991;Moore et al, 1991;FitzSimmons et al, 1995;Rossetto, 2001).…”
Section: Introductionmentioning
confidence: 99%